Analysis of genes involved in the PI3K/Akt pathway in radiation- and MNU-induced rat mammary carcinomas. (13th October 2016) - Showler, Kaye; Nishimura, Mayumi; Daino, Kazuhiro; Imaoka, Tatsuhiko; Nishimura, Yukiko; Morioka, Takamitsu; Blyth, Benjamin J.; Kokubo, Toshiaki; Takabatake, Masaru; Fukuda, Maki; Moriyama, Hitomi; Kakinuma, Shizuko; et al.
Abstract: The PI3K/AKT pathway is one of the most important signaling networks in human breast cancer, and since it was potentially implicated in our preliminary investigations of radiation-induced rat mammary carcinomas, our aim here was to verify its role. We included mammary carcinomas induced by the chemical carcinogen 1-methyl-1-nitrosourea to determine whether any changes were radiation-specific. Most carcinomas from both groups showed activation of the PI3K/AKT pathway, but phosphorylation of AKT1 was often heterogeneous and only present in a minority of carcinoma cells. The negative pathway regulator Inpp4b was significantly downregulated in both groups, compared with in normal mammary tissue, and radiation-induced carcinomas also showed a significant decrease in Pten expression, while the chemically induced carcinomas showed a decrease in Pik3r1 and Pdk1. Significant upregulation of the positive regulators Erbb2 and Pik3ca was observed only in chemically induced carcinomas. However, no genes showed clear correlations with AKT phosphorylation levels, except in individual carcinomas. Only rare carcinomas showed mutations in PI3K/AKT pathway genes, yet these carcinomas did not exhibit stronger AKT phosphorylation. Thus, while AKT phosphorylation is a common feature of rat mammary carcinomas induced by radiation or a canonical chemical carcinogen, the mutation of key genes in the pathways or permanent changes to gene expression of particular signaling proteins do not explain the pathway activation in the advanced cancers. Although AKT signaling likely facilitates cancer development and growth in rat mammary carcinomas, it is unlikely that permanent disruption of the PI3K/AKT pathway genes is a major causal event in radiation carcinogenesis.